"It gave me so much confidence": First‐time U.S. mothers' experiences with antenatal milk expression. Issue 4 (23rd May 2019) - Demirci, Jill R.; Glasser, Melissa; Fichner, Jessica; Caplan, Erin; Himes, Katherine P.
Abstract: Antenatal milk expression (AME) involves maternal hand‐expression, collection, and storage of breast milk during pregnancy for the purposes of reducing the early formula use in breastfed infants. AME is not widely practiced in the United States, despite its growing popularity elsewhere. In this study, we examined the experiences of first‐time mothers recruited from a U.S. midwife practice who engaged in AME within the context of a pilot randomized controlled trial. The AME intervention involved demonstration and practice of AME with a lactation consultant beginning at 37 weeks of gestation, reinforcement at weekly study visits until delivery, and daily home practice. Nineteen women participated in a semistructured interview at 1–2 weeks postpartum regarding their study experiences. Major themes included (1) perceived benefits and impact of AME, (b) AME implementation, and (c) use of AME milk. Women perceived multiple benefits of AME, most notably that it increased their confidence that they would be able to make milk and breastfeed successfully postpartum. Women expressed some concern that no/little milk expressed could be indicative of postpartum milk production problems. Regarding implementation, women found that the AME protocol fit well into their daily routine. There was mixed feedback regarding comfort with practicing AME in the presence of partners. Reasons for postpartum use of AME milk varied; barriers to provision included inadequate milk storage options at the birth hospital and unsupportive hospital providers/staff. With few caveats, AME appears to be an acceptable breastfeeding support intervention among a sociodemographically homogeneous group of first‐time mothers in the United States.